2017
DOI: 10.4274/jus.1140
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fungal Infection Following Penile Prosthesis Implantation: A Case Report

Abstract: Infection is one of the most devastating complications of penile prosthesis implantation. Although the infection prevalence have decreased owing to new technologies and growing surgical experience, it is still a troublesome situation. We present a 50-year-old male patient who had necrotizing fungal infection after penile prosthesis implantation caused by Trichosporon asahii. Keywords: Fungi, infection, necrosis, penile prosthesis, Trichosporon asahii Enfeksiyon, penil protez implantasyonunun en tahrip edici ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies reporting cases of infection following PP surgery demonstrated an increasing proportion of infections due to atypical organisms including more fungi. Case studies dating back to 1988 have reported PP-related Candida Albicans abscesses both locally within the corporal tissue and in more distant organs, e.g., renal tissue [11][12][13].…”
Section: Prevalence Of Fungal Infections Following Pp Implantation Su...mentioning
confidence: 99%
“…Studies reporting cases of infection following PP surgery demonstrated an increasing proportion of infections due to atypical organisms including more fungi. Case studies dating back to 1988 have reported PP-related Candida Albicans abscesses both locally within the corporal tissue and in more distant organs, e.g., renal tissue [11][12][13].…”
Section: Prevalence Of Fungal Infections Following Pp Implantation Su...mentioning
confidence: 99%